Supporting and Inhibiting Factors for Implementing the Independent Curriculum for Fine Arts - Ningsih, Putri; Prasetyo, Abdul Rahman (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2024)
The independent curriculum is a learneru dar-centered learning approach, which provides freedom for them to develop talents according to their interests. However, in its implementation, there are problems related to supporters in implementing the curriculum used now, especially in Fine Arts learning at UM Laboratory Junior High School. The purpose of this study is to describe what are the supporting factors, inhibiting factors, and implementation strategies for the independent curriculum in fine arts learning at UM Laboratory Junior High School. The method used is a qualitative method using a case study approach according to Miles and Huberman, using three data collection techniques, namely observation, interviews, and documentation. The results of the study obtained a description of the supporting factors at the school, namely adequate facilities, between teachers collaborating in designing teaching devices, teachers getting training, parental support, and the use of technology in learning, inhibiting factors at school teachers are difficult in classroom management, time constraints, restrictions on the use of technology, and teachers are difficult to motivate students who lack interest in art learning, the strategy of these obstacles, namely, teachers always motivate students and persuade gradually until students want to do assignments, if the teacher is unable then the teacher will contact the parents, the school tries to minimize the time for participants in the class.